FROM A SEMIOTIC TO AN HERMENEUTIC BY RESEARCHING CORPORAL PRACTICES - Crisorio, Ricardo (2014)
This paper discusses the idea of an essence, or even a property, of Physical Education. For this matter, it follows several authors (mainly Foucault) who show that there is no essential union  between signs and what they signify; which relate infinitely between themselves; in sum, that there is an irreducible opening that makes the sign already an interpretation (instead of showing what it signifies), and makes impossible finding an essence (as something that is outside the interpretation), not only in Physical Education, but in any ambit. From here, two questions arise: the one that asks who interprets, that means, since there is no final and indisputable truth, who, and from which position, makes an interpretation; and the one that understands the interpretation must always be reinterpreted, always giving space to different readings. This does not mean that there is no truth, but that it is always historical and, then, political.